Effects of First Diagnosed Diabetes Mellitus on Medical Visits and Medication Adherence in Korea - Hyeongsu KIM; Soon-Ae SHIN; Kunsei LEE; Jong-Heon PARK; Tae Hwa HAN; Minsu PARK; Eunyoung SHIN; Hyoseon JEONG; Jung-Hyun LEE; Hyemi AHN; Vitna KIM (Iranian Journal of Public Health, 2018)
Background: The National Health Insurance Service (NHIS) conducted a screening test to detect chronic diseases such as hypertension and diabetes in Korea. This study evaluated the effects of health screening for DM on pharmacological treatment.